2022
DOI: 10.1097/prs.0000000000009030
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Heating and High-Intensity Focused Electromagnetic Treatment Delivered Simultaneously: The First Sham-Controlled Randomized Trial

Abstract: Background: Radiofrequency-based and high-intensity focused electromagnetic (HIFEM)-based devices have proved effective and safe for abdominal body shaping. Radiofrequency is known to reduce adipose tissue, whereas HIFEM treatment is effective for muscle definition. The authors investigated the efficacy of a novel device delivering synchronized radiofrequency and HIFEM treatment simultaneously for abdominal toning and fat reduction. Methods: Seventy-two patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 23 publications
(33 reference statements)
0
60
0
Order By: Relevance
“…All studies with surveys reported high patient satisfaction. 5,6,10,[12][13][14]20,22,26 Photographs typically depicted modest results (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies with surveys reported high patient satisfaction. 5,6,10,[12][13][14]20,22,26 Photographs typically depicted modest results (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). 5,10,11,[14][15][16]20,22 By contrast, the sham-controlled study by Samuels et al 6 showed a dramatic reduction in the abdominal profile (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electromagnetic field devices, particularly the High Intensity Focused Electromagnetic Field (HIFEM), include the latest generation of dermatological technologies. The FDA permission for these technologies includes intended uses such as “stimulating neuromuscular tissue for muscle mass excitation in the legs or arms” and improving and strengthening abdominal tone [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%